2007
DOI: 10.1007/s00702-007-0828-z
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory deficits in attention-deficit/hyperactivity disorder are independent of basic processing efficiency and IQ

Abstract: In highlighting the significant, but limited, role of inhibitory deficits in ADHD, these results are consistent with recent accounts that emphasize the neuropsychological heterogeneity of this condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
45
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 33 publications
3
45
0
1
Order By: Relevance
“…In parity with this result, Van der Meere et al (2005) found that only RT variability, but not inhibition or delay aversion, was associated with ADHD symptoms. Independent effects of inhibition, when controlling for RT variability, have however, been found in some previous studies (Bitsakou et al 2008, Klein et al 2006. Although the exact nature of the relation between state regulation and other neuropsychological constructs in the prediction of ADHD symptoms is far from clear, the little empirical evidence available suggests that RT variability represents an independent neuropsychological pathway rather than a more generalized cognitive deficit that underpins other neuropsychological impairments in children with ADHD (e.g., Sergeant 2000Sergeant , 2005.…”
Section: Multiple Neuropsychological Pathways In Adhdmentioning
confidence: 93%
“…In parity with this result, Van der Meere et al (2005) found that only RT variability, but not inhibition or delay aversion, was associated with ADHD symptoms. Independent effects of inhibition, when controlling for RT variability, have however, been found in some previous studies (Bitsakou et al 2008, Klein et al 2006. Although the exact nature of the relation between state regulation and other neuropsychological constructs in the prediction of ADHD symptoms is far from clear, the little empirical evidence available suggests that RT variability represents an independent neuropsychological pathway rather than a more generalized cognitive deficit that underpins other neuropsychological impairments in children with ADHD (e.g., Sergeant 2000Sergeant , 2005.…”
Section: Multiple Neuropsychological Pathways In Adhdmentioning
confidence: 93%
“…1 These include executive dysfunction ((EDF 2 ) e.g, inhibitory 3 and working memory (WM 4 ) deficits), non-executive deficits (e.g. perception 5 ; memory 6 ; timing 7 ) and alterations in motivational processes.…”
mentioning
confidence: 99%
“…In this sense the results are highly consistent with recent studies showing (i) only moderate diagnostic power of individual neuropsychological tests (Riccio & Reynolds, 2001;Romine et al, 2004), (ii) improved performance of multivariate models (Berlin et al, 2004;de Zeeuw, et al, 2008) and (iii) theoretical models that emphasize the neuropsychological heterogeneity of the condition and the possibility of multiple pathways between originating causes and disorder expression (Sonuga-Barke, 2002;2003;Nigg, 2006). The current data, clearly encourage the exploration of alternative neuropsychological bases in ADHD such as inhibitory control (Bitsakou, et al, 2008), state regulation (Sergeant, 2005), and temporal processing (Toplak et al, 2006).…”
mentioning
confidence: 99%